Prevalence and known risk factors for overweight and obesity in adolescents in urban Maseru - Seheri, Lisemelo (University of the Free State, 2012)
English: Chronic diseases of lifestyle (cardiovascular disease, Type 2 diabetes, cancer) remain the leading causes of death and illness among people in both developed and developing countries. The prevalence of obesity, which is one of the main risk factors for developing these diseases, has risen to epidemic proportions. Overweight and obesity are becoming more and more prevalent at ever younger ages, trigerring health consequences in children and adolescents that track into adulthood. No data is available yet regarding overweight and obesity in Lesotho. A cross-sectional descriptive study was conducted to determine the prevalence and known risk factors for overweight and obesity in adolescents in urban Maseru, Lesotho. A sample size of 251 students (125 boys and 126 girls) was randomly selected from the 20 schools in urban area of the Maseru district. Only learners 16-year olds in Form 4 were included in the study due to limited resources. The final study population was 221 students. Approval to undertake the study was obtained from the Ethics Committee of the Faculty of Health Sciences at the University of the Free State. Permission was also required from the Chief Inspector in the Ministry of Education and Training and the heads of the selected schools. Signed .informed consent and assent was obtained from the parents and the learners, respectively. Structured interviews were conducted on the school premises, using a questionnaire to record demographic data, birth weight and height, lifestyle factors, diet history, physical activity and knowledge, attitudes and practices (KAP) in nutrition. The participants were weighed and measured to calculate their body mass index (BMI). Reliability interviews of 10% of the sample were conducted one month after the initial interview. Data collected were described as means and standard deviations and percentages. Pearson correlation analyses were performed to evaluate associations between parameters. The analysis was performed be the Department of Biostatistics at the University of the Free State. The results of this study revealed that the prevalence of overweight/obesity in adolescents in urban Maseru is lower than in SA, with females having higher prevalences (11.3% and 20%, respectively) than (2.1 % and 4.1 %, respectively). When comparing different standards for interpretation of results, the World Health Organisation (WHO) standards identified more overweight males (4.1 %) than females (20.0%) than the Centre of Disease Control and prevention (CDC) growth standards (3.1 % males and 16% females) and the International Obesity Task Force (lOTF) cut-off-points. When using a 24-hour recall, the majority of participants reported lower than the recommended intakes of fruits (86.4%) and vegetables (91.4%), and dairy products (91.0%), but higher than the recommended intakes of grains and starchy vegetables (74.7%). These trends were confirmed by the results of a food frequency questionnaire which revealed that fruits, vegetables, diary, meat and pulses were not consumed on a daily basis. Maize porridge (56.1 %) and bread (63.8%) were eaten by most on a daily basis. Margarine/butter/oil, salt and sugar were consumed daily by most. Most students (54.3%) bought food (including processed meat which are high in fat and salt) from the tuck shop on a weekly basis, while 18.6% did so daily. Despite poor eating habits, most participants had adequate nutrition knowledge and a negative attitude towards obesity. The majority of participants were vigorously to moderately physically active, but no one out of five (22.7%) were not active. The majority of participants watched TV for less than 4 hours per a day, while computer usage outside school hours was low. Energy intake and physical activity were identified to be significantly associated with BMI. Alcohol and cigarette usage were lower than among South African adolescents. The results indicate that overweight and obesity, and the associated risk factors are emerging problems among Lesotho adolescents. Lesotho is apparently following South Africa in undergoing a nutrition transition from a traditional diet high in unrefined grains, fruits an vegetables, to a more westernised diet high in fat, salt and sugar; accompanied by increased alcohol and cigarette usage, while more sedentary practices such as TV watching are also emerging. Data collected from this study will be used as baseline data to enable individuals, health care teams and/or government of Lesotho to design programmes to address these identified problems.

Afrikaans: Chroniese leefstylsiektes (kardiovaskulere siektes, Tipe 2 diabetes, kanker) bly die vernaamste oorsake van dood en siekte onder mense in biede ontwikkelde en ontwikkellende lande. Die voorkoms van vetsug, wat een van die hoofoorsake van hierde chroniese siekte is, het werelwyd tot epidemiese afmetings gestyg. Oormassa en vetsug kom al meer dikwels op al hoe jonger ouderdomme voor, en sneller gesondheidsrisiko's in kinders en adolessente wat deurloop tot in volwassenheid. Geen data is tans beskikbaar oor oormassa en vetsug onder adolessente in Lesotho nie. 'n Dwarssnit observasiestudie is uitgevoer om die voorkoms en bekende risikofaktore van oormassa en vetsug onder adolessente in stedelike Maseru te beskryf. 'n Steekproef van 251 leeders (125 seuns en 126 meisies) is ewekansig uit die 20 skole in die stedelike area van die Maseru distrik getrek. Weens beperkte hulbronne is net 16-jarige leeders in Form 4 in die studie ingesluit. Die finale studiepopulasie het uit 221 leeders bestaan. Toestemming is van die Etiekkomitte van die Universiteit van die Vrystaat verkry. Toestemming os ook van die Hoof-inspekteur van die Ministrie van Onderwys en van die skoolhoofde van die geselekteerde skole verkry. Getekende ingeligde is van die ouers en die leeders verkry. Gestruktureerde onderhoude is op die skoolgronde met die leeders gedoen en 'n vraelys is gebruik om demografiese data, geboortemassa en -lengte, leefstylfaktore, dieetgeskiendenis, fisiese aktiwiteitsvlakke, asook kennis, houdings en praktyke tov voiding, op record te stel. Die leeders is geweeg en gemeet om hul ligaamsmassa indekse (LMI) te bereken. Onderhoude is op 10% van die steekproef een maand na die insielle onderhoud, herhaalom betroubaarheid te bepaal. Data is an gemiddeldes en standaarfwyking en persentasies beskryf en Pearson korrelasies is gedoen om assosiasies tussen parameters te evalueer. Die statistiese analise is deur die Department Biostastistiek van die Vrystaat uitgevoer. Die resultane van hierdie studie het aangetoon dat die voorkoms van oormasa en vetsug laer onder adolessente in Lesotho as in Suid-Afrika is, met meisies wat hoer voorkomssyfers (I 1.3% en 20%, respektiewelik) as seuns (2, I% en 4.1 %, respektiewelik) gehad het. Die WGO groeistandaarde het meer oormassa seuns (4.1 %) en meisies (20.0%) as die CDC-groeistandaarde het meer oormassa seuns (3.1 % seuns en 16% meisies) en die IOTF-afsnypunte geidentifiseer. Die meerderheid van die leeders het in 'n gewoontelike 24-uur herroep vraelys, laer as aanbevole innames van vrugte (86.4%) en groente (91.4%) en suiwelprodukte (91.0%), maar hoer as aanbevole innames van grane en styselgroentes (74.7%) gerapporteer. Die voedselfrekwensievraelys het hierde neigings bevestig, deur aan te toon dat vrugte, groente, suiwel, vleis en puelgroente nie deur die meerderheid van die meeste leeders daagliks genuttig Die meeste leeders het wel daagliks margarine/botter/olie, sout en suiker ingeneem. Die meeste leeders (54.3%) koop weekliks by die skoolsnoewinkels kos (insluitende geprosesseerde vleis wat ryk in vet en sout is), terwyl 18.6% dit daagliks doen. Ten spyte van swak eetgewoontes, het die meeste leeders egter voldoende voedingskennis en 'n negatiewe houding jeens vatsug gehad. Die meerderheid van die leeder was matig tot baie aktief, maar een uit vyf meisies (22.5%) was nie aktief nie. Die meerderheid leerders kyk minder as 4 ure per dag TV, terwyl die gebruik van rekenaars buite skoolure lag is. Energie en fisiese aktiwiteit het betekenisvol met LMI gekorreleer. Alkoholgebruik en sigaretrokery het in 'n mindere mate as onder Suid-Afrikaanse adolessente voorgekom. Die resulate dui daarop dat oormassa en vetsug, en die geassosieerde risikofaktore, wel ontluikende probleme onder adolessente in Lesotho is. Lesotho volg skynbaar in Suid-Afrika se voetspore mbt die voedingoorgang van die tradisionele diet hoog in onverfynde grane, vrugte en groente, na meer 'n westerse eetpatroon hoog in vet, sout, en suiker, met gepaardgande toenames in alkoholgebruik en sigaretrokery, terwyl aktiewe gedrag soos TV -kyk ook aan die toeneem is. Die resultate van hierdie studie sal as basislyndata gebruik word om individue, gesondheidsorgspanne en/of die regering van Lesotho instaat te stelom programme te ontwikkel om die geidentifiseerde problem aan te spreek.
Keywords: Obesity in adolescence -- Maseru; Teenagers -- Nutrition -- Maseru; Dissertation (M.Sc. (Nutrition and Dietetics))--University of the Free State, 2012